Characterization of complete mitochondrial genome of Oreonectes furcocaudalis (Cypriniformes, Balitoridae, Nemacheilidae). Issue 1 (1st January 2017) - Luo, Fuguang; Huang, Jie; Liu, Junling; Situ, Ling; Liu, Xia; Wen, Yanhong
Abstract: Oreonectes furcocaudalis is a rare cave-dwelling loach that lives in the karst cave of Rongshui and Rong'an county, Southwestern China. In this study, the complete mitochondrial genome of O. furcocaudalis is sequenced using the Illumina Hiseq4000 platform with de novo strategy, with a circular molecule of 16, 569 bp in size (GenBank accession number KX778472). It contains 13 protein-coding, 2 ribosomal RNA, 22 transfer RNA genes, and a 917 bp control region. Phylogenetic tree based on the complete mitogenome show that Oreonectes as a clade is close to the genus Lefua and Homatula.